Research progress on the therapeutic effects of effective components of traditional Chinese medicine in the treatment of gastric cancer precursors through modulation of multiple signaling pathways - Han, Lichao; Ma, Yijia; Wu, Weidong; Ni, Qianyue; Xie, Jingri; Huang, Yan; Jin, Qiuyu; Wu, Lili; Zhang, Yang (Frontiers in Oncology, 2025)
Precancerous lesions of the stomach (PLGC), a critical stage in gastric cancer development, have garnered significant attention for its prevention and treatment. PLGC refers to a series of pathological and histological changes preceding cancer. Due to its complex pathogenesis and multi-factor influence, no currently existing drug can effectively prevent or delay this process. Therefore, identifying a safe and effective treatment method remains an important research focus. In recent years, traditional Chinese medicine has demonstrated unique advantages and potential in PLGC treatment. Many studies have focused on the regulation of traditional Chinese medicine’s active ingredients on relevant signaling pathways. Studies show active ingredients can regulate cell proliferation, apoptosis, differentiation, autophagy, oxidative stress, and inflammatory response via multi-target, multi-pathway intervention of key signaling pathways like hypoxia-inducible factor 1 (HIF-1α), nuclear factor kappa-B (NF-κB), wingless-type MMTV integration site family/beta-catenin (Wnt/β-catenin), phosphoinositide 3-kinases/Protein kinase B (PI3K/AKT), Sonic Hedgehog (Shh), Janus kinase/signal transducer and activator of transcription (JAK/STAT), mitogen-activated protein kinase (MAPK), nuclear factor erythroid 2-related factor 2 (Nrf2), and more, thereby delaying or reversing PLGC progression. This paper summarizes and sorts research on the regulation of these pathways by traditional Chinese medicine’s active ingredients, seeking to provide a theoretical basis and medication reference for PLGC treatment with traditional Chinese medicine.